Capecitabine safety profile, innovative and generic adjuvant formulation of nonmetastatic colorectal cancer - Julia Sánchez-Gundín; Ana Isabel Torres-Suárez; Ana María Fernández-Carballido; Dolores Barreda-Hernández (Elsevier, 2019)
Objective: To analyze adverse reactions in patients with nonmetastatic colorectal cancer due to treatment with either innovative or generic capecitabine and/or to the chemotherapeutic regimen employed, to the capecitabine alone, or in combination with oxaliplatin (XELOX). Method: Descriptive retrospective study carried out in a secondary level hospital in two study periods (November 2013-April 2014 and August 2016-May 2017). The collected variables were: exposure (chemotherapy scheme and/or received medication), control (demographics, disease and treatment data), and response (adverse reactions). The statistical analysis of data was performed with the SPSS® 15.0 program. Results: Fifty patients were included. According to the administered chemotherapeutic scheme, statistically significant differences were found in the appearance of palmar-plantar erythrodysesthesia, which is more frequent with monotherapy (p < 0.05), and neurotoxicity, thrombocytopenia and neutropenia, which is more frequent with XELOX (p < 0.05). Concerning the capecitabine drug administered, no statistically significant differences were found in the studied adverse reactions. Conclusions: The safety profile of two capecitabine formulations - innovative and generic- appears to be associated with the chemotherapy scheme employed, and not the drug itself. Most palmar- plantar erythrodysesthesia for monotherapy is likely due to the higher dose of capecitabine used in said scheme. The increase in neurotoxicity, thrombocytopenia and neutropenia for XELOX is probably due to cumulative toxicity of two antineoplastic drugs.